Success stories in Caribbean innovation & entrepreneurship (CCST Port of SpainTT, 2010)
Charts the development of 30 enterprises of varying sizes, and the myriad ways that they have been creative and resourceful in their entrepreneurial activities to generate new and successful businesses in the region.
Keywords: ENTREPRENEURSHIP